2023
DOI: 10.1108/sgpe-04-2022-0032
|View full text |Cite
|
Sign up to set email alerts
|

Social support resilience as a protective mental health factor in postgraduate researchers’ experiences: a longitudinal analysis

Abstract: Purpose This study aims to examine the following across a six-month period in post-graduate research (PGR) students: mental health and well-being; the effect of academic pressures on depression, anxiety and well-being; and the extent to which psychological resilience buffered against academic pressures. Design/methodology/approach This was a longitudinal questionnaire study with predictor variables of six types of academic pressure, outcome variables of depression, anxiety and well-being, and a moderator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Higher resilience was predictive of lower anxiety and depression, better sleep and wellbeing, and reduced suicidal behaviours. More recently, Gooding et al [31] conducted a longitudinal analysis which supported these findings. Their results indicated that baseline resilience buffered against academic challenges during doctoral research.…”
Section: Individual Factorsmentioning
confidence: 77%
See 2 more Smart Citations
“…Higher resilience was predictive of lower anxiety and depression, better sleep and wellbeing, and reduced suicidal behaviours. More recently, Gooding et al [31] conducted a longitudinal analysis which supported these findings. Their results indicated that baseline resilience buffered against academic challenges during doctoral research.…”
Section: Individual Factorsmentioning
confidence: 77%
“…Further survey data document this association, as self-belief has been found to be a key determinant of coping well with the demands of doctoral research [35], and negative appraisals of academic challenges has been found to predict anxiety [31]. The survey conducted by Casey et al [36] used the scale developed by Juniper et al [37] to explore the factors underpinning wellbeing in doctoral research.…”
Section: Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding coincided with literature. [21][22][23] A recent study 23 concluded that social support and resilience had buffering effect on demanding medical training life and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated a high prevalence of stress [5], psychological distress [6,7], and depression and anxiety [8] in doctoral students at UK universities. Poor resilience to stress has been identified in this population [9][10][11], which also contributes to poorer mental health outcomes. Further, research has explored how this contributes to absence and attrition in postgraduate research degrees in the UK [12].…”
Section: Introductionmentioning
confidence: 98%